2011
DOI: 10.1055/s-0030-1271084
|View full text |Cite
|
Sign up to set email alerts
|

In VitroEffect of Valepotriates Isolated fromValeriana glechomifoliaon Rat P-Type ATPases

Abstract: Valepotriates are iridoids found in variable amounts in Valerianaceae and might be among the bioactive compounds which confer anxiolytic properties to the Valeriana species. On the other hand, unspecific cytotoxicity has also been described. Presently, however, no particular molecular target has been defined for these compounds. Here we studied the effect of valtrate, acevaltrate, and 1- β-acevaltrate isolated from Valeriana glechomifolia on the enzymatic activity of rat P-type ATPases. Valepotriates did not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The brain tissues, used as a source of ouabain-sensitive (α 2 /α 3 ) Na,K-ATPase isoforms, were homogenized in 250 mM buffered sucrose, 2 mM dithiothreitol, 0.1 mM PMSF and 5 mM Tris/HCl (pH 7.4) with a motor-driven Teflon Potter-Elvehjem homogenizer. Subsequently, chaotropic treatment with 2 M KI was performed for 1 h under constant stirring, followed by centrifugation three times at 100,000× g for 1 h. The final pellet was resuspended in 250 mM sucrose, 0.1% sodium deoxycholate and 20 mM maleate/Tris (pH 7.4), then stored overnight at −20°C and subjected to differential centrifugation after thawing [67] . The pellets were resuspended in the same buffer without PMSF and stored in liquid N 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The brain tissues, used as a source of ouabain-sensitive (α 2 /α 3 ) Na,K-ATPase isoforms, were homogenized in 250 mM buffered sucrose, 2 mM dithiothreitol, 0.1 mM PMSF and 5 mM Tris/HCl (pH 7.4) with a motor-driven Teflon Potter-Elvehjem homogenizer. Subsequently, chaotropic treatment with 2 M KI was performed for 1 h under constant stirring, followed by centrifugation three times at 100,000× g for 1 h. The final pellet was resuspended in 250 mM sucrose, 0.1% sodium deoxycholate and 20 mM maleate/Tris (pH 7.4), then stored overnight at −20°C and subjected to differential centrifugation after thawing [67] . The pellets were resuspended in the same buffer without PMSF and stored in liquid N 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, Maurman and colleagues demonstrated that a valepotriate fraction from V. glechomifolia displays anxiolytic and sedative effects and impairs behavioral parameters related to recognition memory in rodents [13]. Moreover, we have shown that diene valepotriates isolated from V. glechomifolia (valtrate, acevaltrate, 1-β-acevaltrate, and 1-β-aceacevaltrate) inhibit Na + /K + -ATPase from the rat brain in vitro [17]. Na + /K + -ATPase is a membrane-bound enzyme made up of a catalytic α subunit and a regulatory β subunit [18].…”
Section: Abbreviationsmentioning
confidence: 60%
“…Most important, this study further supports the hypothesis that the enzyme Na + /K + -ATPase may constitute one of the valepotri-atesʼ molecular targets. In a previous work, we have demonstrated that diene valepotriates (valtrate, acevaltrate, and 1-β-acevaltrate) isolated from V. glechomifolia presented inhibitory activity towards rat cerebral Na + /K + -ATPase in vitro [17]. Herein, we show for the first time that VAL increases the activity of Na + /K + -ATPase and protein expression of the α2 isoform in the cerebral cortex of mice after a repeated treatment.…”
mentioning
confidence: 56%
“…AV and BAV are isomers, even though their structures have been confused in the literature [ 7 , 30 ]. Thus, LC-MS, UV and NMR analyses were performed to confirm their chemical structures.…”
Section: Resultsmentioning
confidence: 99%